2016
DOI: 10.1016/j.jbior.2015.09.006
|View full text |Cite
|
Sign up to set email alerts
|

Sphingosine-1-phosphate and estrogen signaling in breast cancer

Abstract: Breast cancer remains the most common malignant disease in women. The estrogen receptor-α (ERα) and its ligand 17β-estradiol (E2) play important roles in breast cancer. E2 elicits cellular effects by binding to ERα in the cytosol followed by receptor dimerization and translocation to the nucleus where it regulates gene expression by binding to ERE response elements. However, it has become apparent that E2 also exerts rapid non-genomic effects through membrane-associated receptors. There is emerging evidence th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
35
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 40 publications
(39 citation statements)
references
References 46 publications
1
35
0
3
Order By: Relevance
“…As key players in normal physiology and in disease, it is unsurprising that there is a large body of evidence demonstrating the contribution of an imbalance in the SphK/S1P rheostat to a plethora of pathological conditions including cancer, diabetes, inflammatory diseases, neurodegenerative diseases (Parkinson's and Alzheimer's), cardiovascular and liver diseases, which have been extensively reviewed [2, 3, 11, 15, 18, 48, 5672]. Although removal of one of the major SphK isozymes is not fatal, as determined in mice with knockout of either SphK1 or SphK2, what these studies have revealed is that loss of one isozyme increases the risk of major health problems including altered vasculature formation [73, 74], impairment in wound healing [75], abnormal islet formation, which could lead to type 1 diabetes [76], and cardiac dysfunction (ischemic) [77], among other complications.…”
Section: Involvement Of Sphk and S1p In The Pathogenesis Of Cancer Anmentioning
confidence: 99%
See 2 more Smart Citations
“…As key players in normal physiology and in disease, it is unsurprising that there is a large body of evidence demonstrating the contribution of an imbalance in the SphK/S1P rheostat to a plethora of pathological conditions including cancer, diabetes, inflammatory diseases, neurodegenerative diseases (Parkinson's and Alzheimer's), cardiovascular and liver diseases, which have been extensively reviewed [2, 3, 11, 15, 18, 48, 5672]. Although removal of one of the major SphK isozymes is not fatal, as determined in mice with knockout of either SphK1 or SphK2, what these studies have revealed is that loss of one isozyme increases the risk of major health problems including altered vasculature formation [73, 74], impairment in wound healing [75], abnormal islet formation, which could lead to type 1 diabetes [76], and cardiac dysfunction (ischemic) [77], among other complications.…”
Section: Involvement Of Sphk and S1p In The Pathogenesis Of Cancer Anmentioning
confidence: 99%
“…Since SphKs have been recognized as major driver proteins in many cancer types, there has been much interest in targeting the overexpression of human SphK1 (hSphK1)/S1P as an anticancer treatment [11, 15, 27, 48, 57, 60, 239, 269276]. However, the design of drugs to inhibit SphK/S1P action has inherent complexities due to the diversity of SphK functions and its important role(s) in normal physiology.…”
Section: Sphk/s1p Designer Drugsmentioning
confidence: 99%
See 1 more Smart Citation
“…Circulating S1P in humans is associated with a negative effect on bone mass, although S1P in osteoblasts promotes growth and survival . Estrogen modulates S1P production in cells including astroglia, breast, and endothelium . In bone, estrogen is essential for skeletal development and maintenance with a mixture of direct and indirect effects on growth and on the balance of bone formation and resorption .…”
Section: Introductionmentioning
confidence: 99%
“…In the last decade, sphingolipid mediators including sphingosine, ceramide and sphingosine-1-phosphate (S1P), S1P receptors (S1PRs), and enzymes of S1P metabolism, have been identified as key modulators of several human pathologies including pulmonary diseases (Natarajan et al, 2013; Ebenezer et al, 2016a), cancers (Pyne and Pyne, 2010; Pyne et al, 2014) including breast cancer (Macziz et al, 2016) and immune responses (Spiegel and Milstien, 2011; Hisano et al, 2012). Among the sphingolipid metabolites, S1P has been shown to have both beneficial and detrimental effect on lung inflammation and vascular integrity.…”
Section: Introductionmentioning
confidence: 99%